Country of origin from a management perspective of emerging market companies - Marzanna K. Witek-Hajduk; Anna Grudecka (International Journal of Management and Economics, 2019)
Objective: The purpose of this paper is to identify the understanding and strategic importance of the country of origin (COO) and its dimensions from the perspective of the emerging market firms. Methods: A qualitative approach was applied using in-depth interviews with 11 informants from owners of emerging market companies of household appliances brands. Key findings: COO is perceived by managers of emerging markets' firms as a multidimensional construct. In addition to the COO dimensions presented in the literature, informants indicate the following: country of technology/innovation origin, country of technical culture, country of service network localization, country of organizational culture origin (COOCO), and country of brand launching (COBL). Country of manufacturing (COM)/assembly/parts is perceived as a strategic imperative, first of all, from the sourcing strategy perspective, and it is less important from the marketing perspective than the country of brand origin (COBO). Originality: This study contributes to existing literature by developing a deeper understanding of the COO dimensions from a perspective of emerging market companies.
Keywords: M16; M31; F23; 650; country of origin (COO); country of brand origin (COBO); emerging markets; international marketing; management perspective